Software quality models: Exploratory review - Pinedo, Lloy; Valles-Coral, Miguel; Navarro-Cabrera, Jorge Raul; Injante, Richard; Cárdenas-García, Ángel; Ruiz-Saavedra, Fernando; García-Rivas-Plata, Cecilia; Flores-Tananta, César Augusto (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: The emerging industrialization of software promotes the continuous development of new evaluation models that adapt to the product’s characteristics and the organizations’ needs. OBJECTIVES: This article aims to identify the software quality models proposed between 2016 and 2020. METHODS: We conducted an exploratory systematic review in the SciELO, IEEE Xplore, and Scopus databases, resulting in 14 research papers proposing new models for assessing software quality. RESULTS: 79% of the research papers were extracted from IEEE Xplore, and 50% of them were authored by individuals affiliated with European institutions. We presented various software quality models focused on assessing both product quality and usability for specific purposes. Additionally, we reported that the proposed models are based on common software quality metrics standards such as CMMI, ISO/IEC 9126, and others. CONCLUSION: The review serves to update the state of the art regarding the software quality models proposed in recent years, which will be valuable for researchers and software developers when seeking evaluation models that align with their specific needs.